Colonial remnants facing the 21st century: Ethnocentrism, racism and marginalization - Vega-Centeno Bocángel, Imelda (1994)
In today's world, the issues of exclusion and racism are of distressing urgency. In civilized Europe, various neo-fascist movements have emerged that develop great aggressiveness towards foreigners, particularly if their physical characteristics are notoriously different —such as North Africans, Asians and Central Africans— and, even worse, if their presence is very noticeable in quantitative terms. , They are then perceived as invaders, whose presence threatens the long-awaited well-being of all.